(untitled) (Journal of Applied Oral Science, 2021)
Gingival conditions and tooth sensitivity of young patients with amelogenesis imperfecta lack in depth studies. This case-control study aimed to compare (1) the gingival inflammation, the presence of enamel defects, and tooth sensitivity in young patients with and without amelogenesis imperfecta and (2) to investigate if any difference exists between subtypes of amelogenesis imperfecta. Methodology: We compared forty-two participants with amelogenesis imperfecta with forty-two controls matched for age, gender, and the number of examined sites. Based on interview, clinical examination, and intraoral photography, we collected data on periodontal conditions, enamel defects and the presence of tooth sensitivity. Comparison tests were performed to investigate if any difference existed between cases and controls; and among cases, between the different subtypes of amelogenesis imperfecta. We performed a post-hoc analysis for any significant difference observed. Results: We observed more gingival inflammation, enamel defects and tooth sensitivity among cases (all p<0.05). Participants with hypocalcified amelogenesis imperfecta had more gingival inflammation, enamel defects, and tooth sensitivity than patients with the hypoplastic and hypomature subtypes (all p<0.05). After adjustment for dental plaque, gingival inflammation was associated with the presence of amelogenesis imperfecta (OR (95%CI) = 1.14 (1.05; 1.24). p<0.01). Conclusion: Gingival inflammation, enamel defect and tooth sensitivity are more frequently observed among young patients with amelogenesis imperfecta, and more specifically among children with the hypocalcified subtype.